Evaluación agronómica de siete variedades introducidas y una variedad local de caña de azúcar (saccharum officinarum) en el alto mayo – san martín - Castillo Vargas, William Del (2005)
Sugar cane is a traditional crop of economic, social and environmental importance for the country. It is grown on the coast, jungle and valleys. However, it is on the coast where the largest planted area is located, because it has climatic and soil conditions, allowing planting and harvesting throughout the year, and exceptional yields. Peru was one of the major sugar exporting countries for their high production volumes exceeding domestic demand. This situation began to reverse in the late 70s by the changes caused by the agrarian reform that impacted negatively on production and crop productivity. The establishment of the cooperative system in the 70s brought the lagging technological innovation culture and decreased efficiency of the industry. As a result, the country became a net importer of sugar in the early 80s. In Peru, cultivation of sugarcane has two very distinct phases; the first stage of growth, in the year of 1974 production levels and productivity were increased until reaching 54 339 ha; 168.93 t cane / ha with an export of 462,171 tonnes of sugar. The second stage of shrinkage of production decreased from 1975 production and productivity, decreasing into a sugar importer country. Currently domestic production is located in the coastal region in 70-80% and the rest between the mountains and forests. In the San Martín Region 2500 has now grown sugarcane, producing for the production of spirits and molasses with a not acceptable return for sugarcane growers. St. Martin has ideal climatic conditions both rainfed and irrigated, for the optimum development of this crop and exceed productivity levels currently obtained with local varieties that do not exceed 50 t / ha of sugar cane. This research was conducted in the area of Alto Mayo, which includes appropriate to enhance and promote the cultivation of sugarcane, rescuing and introducing improved skills PGR soil and climatic conditions; in this regard is very important to conduct research in this important crop in the evaluation of agronomic and industrial parameters, local and introduced varieties, and determine the best choice for use in developing future related research. Traductor de Google para empresas:Google Translator ToolkitTraductor de sitios webtest Desactivar traducción instantáneaAcerca del Traductor de GoogleMóvilComunidadPrivacidadAyudaDanos tu opinión